PENGARUH ROI, EPS, DAN DPS TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN DI BEI - Virginia Alicia; Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to empirically examine the effect of Return On Investment, Earning Per Share, and Dividend Per Share on stock prices. The subjects of this research are the banking sectors listed on the Indonesia Stock Exchange (IDX) for the year 2017-2019. The sampling technique used was purposive sampling, with data samples obtained from are 14 companies. The data processing technique used is multiple regression analysis assisted by Microsoft Excel 2016 and the E-Views version 11 program. The results of this study indicate that Earning Per Share have a positive and significant effect on stock price, while Return On Investment and Dividend per share have a negative and no significant effect on stock price. The implications of this research need to increase the company’s financial performance and intensify company profit. Therefore, company stock price also increased.